Trade Analysis and Prediction in Dark web - Eliazer, M.; Gupta, Shruti; Gupta, Bharti (International Journal of Psychosocial Rehabilitation, 2020)
The non-referenced web is estimated five hundred times the width of the web's surface. Dark web accounts for about a few percentage of the anonymous web and contains all types of criminal activities: drug trafficking, counterfeiting, hacking, etc. Dark Net Markets (DNM) are e- markets usually hosted as Tor hidden networks offering escrow services between buyers and sellers trading in Bit coin or other crypt currencies, usually for marketing of drugs or related illegal/regulated goods; Agora was one of the most common DNMs. Agora was a dark net market that hosts on the Tor network itself, launched in 2013 and due to some reasons it was shut down in August 2015. In this paper we propose analyzing and predicting the trade in a particular Dark Web Market (Agora) using neural networks